Microwave-assisted atmospheric pressure plasma polymerization of hexamethyldisiloxane. (20th June 2016) - Matsubayashi, Toshiki; Hidaka, Hiroki; Muguruma, Hitoshi
Abstract: Microwave-assisted atmospheric pressure plasma polymerization is presented. A system with a re-entrant microwave cavity realizes simple matching, stable plasma, and free space under the orifice of plasma steam. Hexamethyldisiloxane is employed as a monomer, while argon is used as a carrier gas. The effective area of the hydrophobic coating film used corresponds to a circle of 20 mm diameter and the deposition rate considered is 5 nm/min. Matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy shows that the coating film has a large molecular weight (>200 kDa), suggesting that a high-crosslinking and three-dimensional polymer matrix is formed and microwave-assisted atmospheric pressure plasma polymerization is fulfilled.